Alterations of the Gut Microbiota in Patients with Diabetic Nephropathy - Lili Zhang; Zhisheng Wang; Xiaona Zhang; Lu Zhao; Jinjin Chu; Haibo Li; Wenchang Sun; Chunjuan Yang; Hui Wang; Wenqing Dai; Shushan Yan; Xiaohua Chen; et al. (Microbiology Spectrum, 2022)
ABSTRACT Diabetic nephropathy (DN) is the primary cause of end-stage renal disease. Accumulating studies have implied a critical role for the gut microbiota in diabetes mellitus (DM) and DN. However, the precise roles and regulatory mechanisms of the gut microbiota in the pathogenesis of DN remain largely unclear. In this study, metagenomics sequencing was performed using fecal samples from healthy controls (CON) and type 2 diabetes mellitus (T2DM) patients with or without DN. Fresh fecal samples from 15 T2DM patients without DN, 15 DN patients, and 15 age-, gender-, and body mass index (BMI)-matched healthy controls were collected. The compositions and potential functions of the gut microbiota were estimated. Although no difference of gut microbiota α and β diversity was observed between the CON, T2DM, and DN groups, the relative abundances of butyrate-producing bacteria (Clostridium, Eubacterium, and Roseburia intestinalis) and potential probiotics (Lachnospira and Intestinibacter) were significantly reduced in T2DM and DN patients. Besides, Bacteroides stercoris was significantly enriched in fecal samples from patients with DN. Moreover, Clostridium sp. 26_22 was negatively associated with serum creatinine (P < 0.05). DN patients could be accurately distinguished from CON by Clostridium sp. CAG_768 (area under the curve [AUC] = 0.941), Bacteroides propionicifaciens (AUC = 0.905), and Clostridium sp. CAG_715 (AUC = 0.908). DN patients could be accurately distinguished from T2DM patients by Pseudomonadales, Fusobacterium varium, and Prevotella sp. MSX73 (AUC = 0.889). Regarding the potential bacterial functions of the gut microbiota, the citrate cycle, base excision repair, histidine metabolism, lipoic acid metabolism, and bile acid biosynthesis were enriched in DN patients, while selenium metabolism and branched-chain amino acid biosynthesis were decreased in DN patients. IMPORTANCE Gut microbiota imbalance is found in fecal samples from DN patients, in which Roseburia intestinalis is significantly decreased, while Bacteroides stercoris is increased. There is a significant correlation between gut microbiota imbalance and clinical indexes related to lipid metabolism, glucose metabolism, and renal function. The gut microbiota may be predictive factors for the development and progression of DN, although further studies are warranted to illustrate their regulatory mechanisms.